RESEARCH MODELS REPAIR DEPARTMENT BAKER IN THE ENVIRONMENT ANYLOGIC - Manokha, L.; Limanska, N.; Rud, S. (Енергетика і автоматика, 2016)
Application of simulation modeling at the design stage technology projects food business, operating in a competitive environment, typical of international practice at the present time. These methods allow the early stages of the modernization project to assess the state of repair of the system bakery and justify the need for modernization.